Impacto da cirurgia bariátrica em dados antropométricos, na ingestão alimentar e nos níveis plasmáticos de citocinas: estudo prospectivo controlado - Viana, Elaine Cristina (2011)
Background. The Bariatric surgery is an alternative for the treatment of morbid obesity because it promotes significant and rapid weight loss and different effects on body composition and on hormone levels synthesized by the digestive tract. However, the knowledge of how different types of bariatric surgery can interfere with the food intake patterns and the levels of inflammatory cytokines, as well as the interaction of all these parameters, needs to be better understood. Objectives. To investigate the impact of two types of bariatric surgery, the banded Roux-en Y gastric bypass (GVAYR group) and the banded vertical gastrectomy (GVA group), on the body weight and body composition, on food intake and on plasma levels of interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF) in obese women after one year of intervention and to compare the effects between the both types of surgeries. Casuistry and Methods. Fifty-five women (36.6 ± 9.0 years) were evaluated, 50.9% (n = 28) in the GVAYR group and 49.1% (n = 27) in the GVA group. All data were assessed on the preoperative and after (1 year later) of the postoperative. We investigated the anthropometric and body composition parameters, the energy, macronutrient and fiber intakes and TNF and IL-6 plasma levels. The Sigma Stat 3.0® software was used for the statistical analysis and we adopted the significance level of p < 0.05. Results. The mean loss of the total body weight was 38.4 ± 7.9 kg (mean = 37.6, min = 18.4, max = 61.7 kg). There was no difference in the percent excess weight loss (% EWL) between both the groups. On the pre and postoperative period there was also no difference to the energy intake and macronutrients between GVA and GVAYR groups, unless to the fiber in the postoperative period that was lower in the GVAYR group (p = 0.045). There were lower caloric and macronutrient intakes and lower intake of protein in both groups on the postoperative period. The higher intake of protein was associated with the higher % EWL (p = 0.021). There was found decreasing of IL-6 for both GVAYR (p = 0.001) and GVA groups (p = 0.002). However, there was no found difference to the TNFα levels on the GVAYR group (p = 0.191). Conclusions. Our results showed that the dietary and protein intakes become deficient in both groups on the postoperative period, and our results suggest xxii that both GVAYR and GVA surgery had success on the body weight loss and induced decreasing of the IL-6 levels